Financial analysis of East Coast Fever control strategies in traditionally managed Sanga cattle in Central Province of Zambia - Minjauw, B.; Rushton, Jonathan; James, A.D.; Upton, M. (Elsevier, 1999)
Five different East Coast fever (ECF)-control strategies (involving ECF immunisation by the infection-and-treatment method) were tested in groups of traditionally managed Sanga cattle in the Central Province of Zambia over a period of 2.5 years. Two groups were under intensive tick control (weekly spraying with acaricide) - one group immunised and the other non-immunised. Two groups were under no tick control - one group immunised and the other non-immunised. The fifth group was under seasonal tick control (18 sprays/year) and was immunised against ECF. The input and output data were used to construct discounted cash flows for each group. The seasonally sprayed and immunised group gave the highest net present value, and the non-immunised group with no tick control, the lowest. A break-even analysis showed that the immunisation costs could rise to US$25.9 per animal before profitability was affected. For herds under intensive tick control, immunisation was of no financial benefit. The results demonstrate the value of immunisation, and indicate the importance of its combination with seasonal tick-control measures.